Florística e fitossociologia de plantas espontâneas emcomunidades antropizadas do cerrado em Minas Gerais - Jordania de Carvalho Macedo Gama (2009)
Cerrado is outstanding concerning biodiversity due to its great vegetalheterogeneity. However, it is estimated that 67% of this biome is considered highly modified and only 20% is found in its original state. Aiming its conservation, this biome is considered a hot spot once it is present in the world areas which are priority to conservation. Among the factors which threaten the biodiversity of Cerrado, spontaneous plants may be considered the second biggest threat. In this context, this work made a floristic and phytosociological survey of spontaneous plants present in the Cerrado regeneration area by Sorgos and Corn EMBRAPA in Sete Lagoas, in the State of Minas Gerais (MG, Brazil), between the years 2007 and 2008. The data collection was done through the plot method. In the total area (60 ha²), 213 collection sites were sampled in 1m² plots, where frames were used to limit the collection area and cuttings to show the place there the sample was taken. For the floristic analysis, plants were organized using the Cronquist classification system, relating the number of sampled individuals, families, genders, species and class. The floristic survey of spontaneous plants evidenced the occurrence of 4214 individuals distributed in 14 species, 11 genders and only 01 botanic family. All the species belong to the Liliopsida and Poaceae classes. The Brachiaria gender was represented by 43% of theindividuals, followed by Melinis(18%). It is relevant to emphasize that among the species, Pennisetum purpureum, Pennisetum pedicellatum, Hypolytrum pungens and Rhynchelytrum repens were found only in the last collection, in May 2008. The relative density allowed evaluating the species distribution in the plots, in which Brachiaria decumbens represented in average, 42% of the species. In the relative frequency, which infers over the plant quantity of each species per area unit, the B. decumbens singles out with an average of 41%. Concerning the concentration of species in the area, the Imperata brasiliensis was the one which presented the relative largest amount. B. decumbenspresented the highest biomass value which justified the highest relativedominance and was also the one which presented the highest importance value index. This study represented the initial knowledge of spontaneous plant dynamics being relevant as a basis to future studies in order to reinforce actions of native flora maintenance and preservation in this area.